Sustainable Digital Marketing Models for Uplifting Micro, Small and Medium Enterprises Product Branding - Grace Yulianti; Mia Christy Patricia; Eri Kusnanto (Proceeding of The International Conference on Economics and Business, 2022)
This research delves into sustainable digital marketing models aimed at enhancing product branding for Micro, Small, and Medium Enterprises (MSMEs). With the burgeoning digital landscape, MSMEs face challenges in effectively leveraging digital platforms for brand promotion. The study's objective is to identify and evaluate sustainable digital marketing strategies conducive to uplifting MSMEs' product branding. Employing a qualitative research design, data is gathered through semi-structured interviews and content analysis of relevant literature. A purposive sampling technique is utilized to select participants from diverse MSME sectors. The data is analyzed using thematic analysis to identify recurring patterns and themes. Preliminary findings highlight the significance of personalized content, social media engagement, and eco-friendly branding in fostering sustainable digital marketing for MSMEs. This research contributes to the discourse on sustainable marketing practices tailored to the unique needs and constraints of MSMEs, offering insights for policymakers, practitioners, and MSME owners seeking to enhance their digital marketing strategies.